Biliary Adenofibroma: A Rare Liver Tumor with Transition to Invasive Carcinoma - Ayham Alshbib; Krzysztof Grzyb; Trygve Syversveen; Henrik Mikael Reims; Kristoffer Lassen; Sheraz Yaqub (Case Reports in Surgery)
Biliary adenofibroma is a rare benign liver tumor with potential for malignant transition. It has a bile duct origin characterized by a complex tubulocystic biliary epithelium with fibrous stroma. MRI features may suggest this uncommon entity, and histological findings can be diagnostic. We report a case of biliary adenofibroma with transformation to an intrahepatic cholangiocarcinoma.